Ferromagnetic behaviour of ZnO: the role of grain boundaries - Straumal, Boris Borisovich; Protasova, Svetlana G.; Mazilkin, Andrei A.; Goering, Eberhard; Schütz, Gisela; Straumal, Petr B.; Baretzky, Brigitte (Beilstein Journal of Nanotechnology, 2016)
The possibility to attain ferromagnetic properties in transparent semiconductor oxides such as ZnO is very promising for future spintronic applications. We demonstrate in this review that ferromagnetism is not an intrinsic property of the ZnO crystalline lattice but is that of ZnO/ZnO grain boundaries. If a ZnO polycrystal contains enough grain boundaries, it can transform into the ferromagnetic state even without doping with “magnetic atoms” such as Mn, Co, Fe or Ni. However, such doping facilitates the appearance of ferromagnetism in ZnO. It increases the saturation magnetisation and decreases the critical amount of grain boundaries needed for FM. A drastic increase of the total solubility of dopants in ZnO with decreasing grain size has been also observed. It is explained by the multilayer grain boundary segregation.
Keywords: ferromagnetism; grain boundaries; zinc(II) oxide (ZnO)

(untitled) - Dietl, T.; Ohno, H.; Matsukura, F.; Cibert, J.; Ferrand, D. (Science, 2000)

(untitled) - Sato, K.; Katayama-Yoshida, H. (Semicond. Sci. Technol., 2002)

(untitled) - Gupta, T. K. (J. Am. Ceram. Soc., 1990)

(untitled) - Onreabroy, W.; Sirikulrat, N.; Brown, A. P.; Hammond, C.; Milne, S. J. (Solid State Ionics, 2006)

(untitled) - Dietl, T. (Nat. Mater., 2010)

(untitled) - Straumal, B. B.; Mazilkin, A. A.; Protasova, S. G.; Stakhanova, S. V.; Straumal, P. B.; Bulatov, M. F.; Schütz, G.; Tietze, T.; Goering, E.; Baretzky, B. (Rev. Adv. Mater. Sci., 2015)

(untitled) - Straumal, B. B.; Mazilkin, A. A.; Protasova, S. G.; Myatiev, A. A.; Straumal, P. B.; Schütz, G.; van Aken, P. A.; Goering, E.; Baretzky, B. (Phys. Rev. B, 2009)

(untitled) - Straumal, B. B.; Mazilkin, A. A.; Protasova, S. G.; Straumal, P. B.; Myatiev, A. A.; Schütz, G.; Goering, E.; Tietze, T.; Baretzky, B. (Philos. Mag., 2013)

(untitled) - Straumal, B. B.; Protasova, S. G.; Mazilkin, A. A.; Straumal, P. B.; Schütz, G.; Tietze, T.; Goering, E.; Baretzky, B. (Beilstein J. Nanotechnol., 2013)

(untitled) - Straumal, B. B.; Mazilkin, A. A.; Protasova, S. G.; Straumal, P. B.; Myatiev, A. A.; Schütz, G.; Goering, E.; Baretzky, B. (Phys. Met. Metallogr., 2012)

(untitled) - Straumal, B. B.; Protasova, S. G.; Mazilkin, A. A.; Schütz, G.; Goering, E.; Baretzky, B.; Straumal, P. B. (JETP Lett., 2013)

(untitled) - Protasova, S. G.; Straumal, B. B.; Mazilkin, A. A.; Stakhanova, S. V.; Straumal, P. B.; Baretzky, B. (J. Mater. Sci., 2014)

(untitled) - Tietze, T.; Audehm, P.; Chen, Y.-C.; Schütz, G.; Straumal, B. B.; Protasova, S. G.; Mazilkin, A. A.; Straumal, P. B.; Prokscha, T.; Luetkens, H.; Salman, Z.; Suter, A.; et al. (Sci. Rep., 2015)

(untitled) - Watanabe, T. (Mater. Sci. Forum, 1997)

High-Angle Grain Boundaries - Gleiter, H.; Chalmers, B. (Pergamon Press, 1972)

Materials Science: An Intermediate Text - Hosford, W. F. (Cambridge Univ. Press, 2006)

(untitled) - Lábár, J. L. (Microsc. Microanal., 2008)

(untitled) - Wang, D. F.; Park, S. Y.; Lee, H. W.; Lee, Y. S.; Lam, V. D.; Lee, Y. P. (Phys. Status Solidi A, 2007)

(untitled) - Gopalakrishnan, N.; Elanchezhiyan, J.; Bhuvana, K. P.; Balasubramanian, T. (Scr. Mater., 2008)

Muon Spin Rotation, Relaxation and Resonance - Yaouanc, A.; Dalmas de Réotier, P. (Oxford Science Publications, 2011)

(untitled) - Dalmas de Réotier, P.; Yaouanc, A. (J. Phys.: Condens. Matter, 1997)

(untitled) - Morenzoni, E.; Prokscha, T.; Suter, A.; Luetkens, H.; Khasanov, R. (J. Phys.: Condens. Matter, 2004)

(untitled) - Prokscha, T.; Morenzoni, E.; Deiters, K.; Foroughi, F.; George, D.; Kobler, R.; Suter, A.; Vrankovic, V. (Nucl. Instrum. Methods Phys. Res., Sect. A, 2008)

(untitled) - Blundell, S. J. (Contemp. Phys., 1999)

(untitled) - Suter, A.; Wojek, B. M. (Phys. Procedia, 2012)

(untitled) - Straumal, B. B.; Protasova, S. G.; Mazilkin, A. A.; Myatiev, A. A.; Straumal, P. B.; Schütz, G.; Goering, E.; Baretzky, B. (J. Appl. Phys., 2010)

(untitled) - Cong, C. J.; Zhang, K. L. (Phys. Status Solidi A, 2006)

(untitled) - Thakur, P.; Chae, K. H.; Kim, J.-Y.; Subramanian, M.; Jayavel, R.; Asokan, K. (Appl. Phys. Lett., 2007)

(untitled) - Abbamonte, P.; Venema, L.; Rusydi, A.; Sawatzky, G. A.; Logvenov, G.; Bozovic, I. (Science, 2002)

(untitled) - Pellegrin, E.; Nücker, N.; Fink, J.; Molodtsov, S. L.; Gutiérrez, A.; Navas, E.; Strebel, O.; Hu, Z.; Domke, M.; Kaindl, G.; Uchida, S.; Nakamura, Y.; et al. (Phys. Rev. B, 1993)

(untitled) - Asokan, K.; Jan, J. C.; Rao, K. V. R.; Chiou, J. W.; Tsai, H. M.; Mookerjee, S.; Pong, W. F.; Tsai, M.-H.; Kumar, R.; Husain, S.; Srivastava, J. P. (J. Phys.: Condens. Matter, 2004)

(untitled) - Guo, J.-H.; Gupta, A.; Sharma, P.; Rao, K. V.; Marcus, M. A.; Dong, C. L.; Guillen, J. M. O.; Butorin, S. M.; Mattesini, M.; Glans, P. A.; Smith, K. E.; Chang, C.; et al. (J. Phys.: Condens. Matter, 2007)

(untitled) - Liu, H.; Yang, J.; Zhang, Y.; Yang, L.; Wei, M.; Ding, X. (J. Phys.: Condens. Matter, 2009)

(untitled) - Wu, P.; Saraf, G.; Lu, Y.; Hill, D. H.; Gateau, R.; Wielunski, L.; Bartynski, R. A.; Arena, D. A.; Dvorak, J.; Moodenbaugh, A.; Siegrist, T.; Raley, J. A.; et al. (Appl. Phys. Lett., 2006)

(untitled) - Lin, Y.; Jiang, D.; Lin, F.; Shi, W. Z.; Ma, X. M. (J. Alloys Compd., 2007)

(untitled) - Karmakar, D.; Mandal, S. K.; Kadam, R. M.; Paulose, P. L.; Rajarajan, A. K.; Nath, T. K.; Das, A. K.; Dasgupta, I.; Das, G. P. (Phys. Rev. B, 2007)

(untitled) - Yermakov, A. Ye.; Uimin, M. A.; Mysik, A. A.; Vykhodets, V. B.; Kurennykh, T. E.; Sokolov, V. I.; Gaviko, V. S.; Schegoleva, N. N.; Gruzdev, N. B. (J. Magn. Magn. Mater., 2007)

(untitled) - Bates, C. H.; White, W. B.; Roy, R. (J. Inorg. Nucl. Chem., 1966)

(untitled) - Trudeau, M. L.; Huot, J. Y.; Schulz, R. (Appl. Phys. Lett., 1991)

(untitled) - Suzuki, K.; Makino, A.; Inoue, A.; Masumoto, T. (J. Appl. Phys., 1991)

(untitled) - Heera, V.; Madhusoodanan, K. N.; Skorupa, W.; Dubois, C.; Romanus, H. (J. Appl. Phys., 2006)

(untitled) - Straumal, B. B.; Dobatkin, S. V.; Rodin, A. O.; Protasova, S. G.; Mazilkin, A. A.; Goll, D.; Baretzky, B. (Adv. Eng. Mater., 2011)

(untitled) - Lemier, C.; Weissmüller, J. (Acta Mater., 2007)

(untitled) - Rizea, A.; Chirlesan, D.; Petot, C.; Petot-Ervas, G. (Solid State Ionics, 2002)

Grain Boundaries in Metals - McLean, D. (Clarendon Press, 1957)

(untitled) - Straumal, B. B.; Mazilkin, A. A.; Protasova, S. G.; Myatiev, A. A.; Straumal, P. B.; Baretzky, B. (Acta Mater., 2008)

(untitled) - Straumal, B.; Baretzky, B.; Mazilkin, A.; Protasova, S.; Myatiev, A.; Straumal, P. B. (J. Eur. Ceram. Soc., 2009)

(untitled) - Straumal, B. B.; Myatiev, A. A.; Straumal, P. B.; Mazilkin, A. A.; Protasova, S. G.; Goering, E.; Baretzky, B. (JETP Lett., 2010)

(untitled) - Straumal, B. B.; Mazilkin, A. A.; Protasova, S. G.; Myatiev, A. A.; Straumal, P. B.; Goering, E.; Baretzky, B. (Phys. Status Solidi B, 2011)

(untitled) - Straumal, B. B.; Mazilkin, A. A.; Protasova, S. G.; Myatiev, A. A.; Straumal, P. B.; Goering, E.; Baretzky, B. (Thin Solid Films, 2011)

(untitled) - Straumal, B. B.; Baretzky, B.; Kogtenkova, O. A.; Straumal, A. B.; Sidorenko, A. S. (J. Mater. Sci., 2010)

(untitled) - Straumal, B. B.; Gust, W.; Watanabe, T. (Mater. Sci. Forum, 1999)

(untitled) - Clarke, D. R. (J. Am. Ceram. Soc., 1987)

(untitled) - Cantwell, P. R.; Ming, T.; Dillon, S. J.; Luo, J.; Rohrer, G. S.; Harmer, M. P. (Acta Mater., 2014)

(untitled) - Kaplan, W. D.; Chatain, D.; Wynblatt, P.; Carter, W. C. (J. Mater. Sci., 2013)

(untitled) - Bueno, P. R.; Varela, J. A.; Longo, E. (J. Eur. Ceram. Soc., 2008)

(untitled) - Luo, J.; Chiang, Y.-M.; Cannon, R. M. (Langmuir, 2005)

(untitled) - Luo, J.; Tang, M.; Cannon, R. M.; Carter, W. C.; Chiang, Y.-M. (Mater. Sci. Eng., A, 2006)

(untitled) - Luo, J. (Crit. Rev. Solid State Mater. Sci., 2007)

(untitled) - Luo, J.; Chiang, Y.-M. (Annu. Rev. Mater. Res., 2008)

(untitled) - Subramaniam, A.; Koch, C. T.; Cannon, R. M.; Rühle, M. (Mater. Sci. Eng., A, 2006)

(untitled) - MacLaren, I. (Ultramicroscopy, 2004)

(untitled) - Dillon, S. J.; Tang, M.; Craig Carter, W.; Harmer, M. P. (Acta Mater., 2007)

(untitled) - Luo, J.; Cheng, H.; Asl, K. M.; Kiely, C. J.; Harmer, M. P. (Science, 2011)

(untitled) - Straumal, B. B.; Mazilkin, A. A.; Baretzky, B. (Curr. Opin. Solid State Mater. Sci., 2016)

(untitled) - Straumal, B. B.; Sauvage, X.; Baretzky, B.; Mazilkin, A. A.; Valiev, R. Z. (Scr. Mater., 2014)